2015
DOI: 10.1002/lt.24073
|View full text |Cite
|
Sign up to set email alerts
|

Surgically placed abdominal wall catheters on postoperative analgesia and outcomes after living liver donation

Abstract: Living donor liver resections are associated with significant postoperative pain. Epidural analgesia is the gold standard for postoperative pain management, although it is often refused or contraindicated. Surgically placed abdominal wall catheters (AWCs) are a novel pain modality that can potentially provide pain relief for those patients who are unable to receive an epidural. A retrospective review was performed at a single center. Patients were categorized according to their postoperative pain modality: int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 43 publications
(90 reference statements)
0
8
0
Order By: Relevance
“…The role of WI with local anesthetics to prevent postoperative pain after open liver surgery was evaluated in ten studies, which included a total of 1412 patients: five compared to TEA (2 RCTs, 2 POS, and 1 RO), four to placebo (RCTs), and one to systemic opioids (RCT) [24][25][26][27][28][29][30][48][49][50]. When compared to TEA, the use of WI produced conflicting evidence: two studies proved WI less effective in pain control than TEA while three studies proved no difference; of the three studies that reported data on LOS, one proved WI was associate with shorter LOS compared to TEA and two recorded no differences; no differences in surgical complication after WI or TEA were reported (Table 3) [24,25,[48][49][50].…”
Section: Trials Assessing Wimentioning
confidence: 99%
“…The role of WI with local anesthetics to prevent postoperative pain after open liver surgery was evaluated in ten studies, which included a total of 1412 patients: five compared to TEA (2 RCTs, 2 POS, and 1 RO), four to placebo (RCTs), and one to systemic opioids (RCT) [24][25][26][27][28][29][30][48][49][50]. When compared to TEA, the use of WI produced conflicting evidence: two studies proved WI less effective in pain control than TEA while three studies proved no difference; of the three studies that reported data on LOS, one proved WI was associate with shorter LOS compared to TEA and two recorded no differences; no differences in surgical complication after WI or TEA were reported (Table 3) [24,25,[48][49][50].…”
Section: Trials Assessing Wimentioning
confidence: 99%
“…In recent decades, continuous or bolus infusions of opioids have been widely used in patient-controlled analgesia after liver resection. However, an increase in analgesic-related side effects, such as sedation, respiratory depression, pruritus, hallucinations and post-operative nausea and vomiting (PONV) has also been reported ( Aydogan et al, 2015 ; Khan et al, 2015 ; Allen et al, 2017 ). It is a challenge for anesthesiologists to perform a technique that could control sedation, analgesia, muscle relaxation, hemodynamic stability during the liver resection, and opioid-sparing analgesia after the surgery.…”
Section: Introductionmentioning
confidence: 99%
“…Although epidural analgesia has historically been the standard of postoperative pain control, recent studies have found that postoperative coagulopathy may put patients at risk for neuraxial hematoma 1, 4. Accordingly, alternative analgesic methods that avoid this risk have been used in the search for safe but effective pain management 4, 5…”
mentioning
confidence: 99%
“…Although single-injection transversus abdominis plane (TAP) blocks can provide excellent analgesia for major abdominal surgery, their primary shortcomings include limitations in dermatomal spread and short duration, with comprehensive analgesia rarely extending beyond 12 hours 6, 7. To extend analgesia duration, some investigators have placed TAP catheters to facilitate infusion of local anesthetic 4, 5. To date, however, this technique has been limited by high failure rates of secondary analgesia 8 …”
mentioning
confidence: 99%